Immune system and damages of liver at chronic hepatites B and C - V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
The aim of review. To present modern data on a role of adaptive immunodefence in development of chronic viral damage of liver and mechanisms of influence of hepatitis viruses B and C (HBV and HCV) on functional activity of cytotoxic lymphocytes (CTL).Original positions. There are some mechanisms of HBV and HCV suppressing effect on immune response parts: exhaustion of virus-specific CTL functional activity as a result of persistence of high concentrations of viral antigens; elevation of activity of regulatory Т-cells; ability HBV to exist in the form of sustained endocellular template – covalently closed circular DNA (ccc DNA); mutations of genome HCV, allowing «to escape» from immune supervision; direct operation action of HCV proteins on Т-cells. The role of activated platelets in immunopathological reactions is also considered at chronic viral liver damage.Conclusion. Application at chronic hepatitis B and C of up-to-date algorithms of antiviral therapy including agents like interferon, ribavirin and nucleotides/nucleosides analogues, does not allow to achieve at significant part of patients long-lasting suppression of viral replication that can result in persistence of replication HBV or HCV, activations of inflammatory and necrotic processes in the liver, clinically manifesting as relapse of hepatitis with subsequent development of liver cirrhosis and hepatocellular carcinoma. Evaluation of efficacy of antiviral therapy with the help of dynamic assessment of viral load and other viral markers yields only indirect representation of activity of pathological process. The recent scientific development offer idea of monitoring of parameters of innate (congenital) and adaptive (acquired) immunodefence at patients with chronic viral hepatites at antiviral treatment, and development of drugs, capable to sustain quantitative and functional stability of virus-specific Т-cells.